Transnational Class Formations, European Crisis and the Silent Revolution. (July 2017) - Gill, Stephen
This article analyzes the European crisis and the reconfiguration of neoliberal governance in light of efforts to deepen integration via what European Union President Manuel Barroso (2010) called a 'Silent Revolution' to create a new 'economic government' that could better manage crises and shape development alternatives. The article places recent developments in a longer-term perspective involving post-Second World War geopolitics, transatlantic class formations, extension of the world market and recent, fundamental crises of capitalism. It argues that in the current situation, the relative unity of Europe's ruling classes contrasts with the relative fragmentation of subaltern forces, mainly along national-popular lines. This situation shapes (but does not necessarily determine) the 'limits of the possible' for political agency in Europe, and it helps explain the persistence of neoliberalism in the European Union in a situation of organic crisis, where the relations of force remain contested, open and politically unstable.